Dynamic voltage threshold adjusted substrate modification technique for complex atypical atrial flutters with varying circuits. Issue 11 (26th September 2020) - Methachittiphan, Nilubon; Akoum, Nazem; Gopinathannair, Rakesh; Boyle, Patrick M; Sridhar, Arun R.
Abstract: Background: Atypical atrial flutter (AFL) is common in patients with postsurgical atrial scar, with macro‐ or microscopic channels in the scar acting as substrate for reentry. Heterogeneous atrial scarring can cause varying flutter circuits, which makes mapping and ablation challenging, and recurrences common. Aim: We hypothesize that dynamically adjusting voltage thresholds can identify heterogeneous atrial scarring, which can then be effectively homogenized to eliminate atypical AFLs. Methods: We studied consecutive patients who presented to Electrophysiology laboratory for atypical AFL ablation with history of atriotomy and included the patients with multiple, varying flutter circuits during mapping in our study. We excluded patients with stable flutter circuit that was sustained and could be localized using traditional entrainment and activation mapping strategy. In the included patients, we performed detailed high‐density voltage map of the atrium of interest. We adjusted voltage thresholds as needed to identify heterogeneity and channels in the scarred regions. A thorough scar homogenization was performed with irrigated smart‐touch ablation catheter. Re‐inducibility of tachycardia, and immediate and long‐term outcomes were studied. Results: Of five studied cases, one was female; age 66 ± 10 years. All five had prior surgical substrate. All the patients had multiple flutter morphologies, which varied as we mapped the AFL. After scar homogenization, tachycardia was not inducible in any patient. No recurrence of flutter was noted during a mean follow‐up duration of 450 ± 27 days. Conclusion: High‐density voltage mapping and homogenization of the scar can be an effective strategy in eliminating complex scar‐mediated atypical AFL with multiple circuits.